Dynamic livelihoods: making the most of rural-urban connections - Garrett, James L. (International Food Policy Research Institute, 2005)
Recent research provides insights into how rural conditions and livelihood strategies are changing, often in response to ongoing processes of economic transformation and urbanization. The research highlights the importance of close connections with urban areas and suggests how policies and programs can support the positive dynamics of change.